Information system for the quantification of financial risk (2017)
The quantification of financial risk such as liquidity risk and others is one of the most frequent concern in the bank and corporative sector, in this sense, the liquidity risk materialization causes big monetary lost when corporations are incapable on give appropriate fulfillment of obligations due to lack of liquid resources. On the other hand, when operational risk is present, there are large losses due to fails on the procedures that adversely affect the functioning of the organization. With the goal of systematize the risk quantification it has implement the Information System Financial Risk Management, which was constructed like a suite of software compound by two applications that facilities the quantification of liquidity risk and operational risk. Nowadays the Information System is used by corporations in Colombian financial sector, who by means of use of tools has been reached the fulfillment the results, avoiding the materialization of negative events. © 2017 AISTI.